Effect of food intake on the pharmacokinetics of rivoceranib in healthy subjects. (6th July 2021) - Sachar, Madhav; Park, Cheol Hee; Pesco‐Koplowitz, Luana; Koplowitz, Barry; McGinn, Arlo
Abstract: Rivoceranib is a selective inhibitor of VEGFR‐2 being developed for the treatment of solid tumor. The objective of the study was to evaluate the effect of food on bioavailability as well as single‐ and multiple‐dose pharmacokinetics (PKs) of 81 and 201 mg doses of rivoceranib. The study was conducted as a two‐part study. In Part 1 (single ascending dose (SAD), open‐label, crossover study design), 2 oral doses of rivoceranib (81 mg or 201 mg) were given to all healthy subjects with a minimum 3‐day washout period between dosing. Part 2 was a multiple ascending dose (MAD), open‐label, crossover design where subjects were divided based on 81 and 201 mg doses. Both doses were administered with and without food in a crossover manner for the SAD and MAD parts. 24 healthy subjects completed Part 1 and 20 subjects completed Part 2. For the 81 mg dose in the SAD and MAD parts of the study, their food effect was not observed. For the 201 mg dose in both parts, food appeared to increase bioavailability by 20%–30% in Part 1, and 30%–40% in Part 2. Median tmax value was delayed when rivoceranib was administered with food at each dose level in both parts of the study. Dose proportionality was confirmed only for the AUC0‐∞  value from Part 1‐fasted cohort but inconclusive for Cmax  and AUC parameters under other dosing regimens. In conclusion, rivoceranib when taken with food delays tmax appears to increase bioavailability at 201 mg dose.